Missions, Matrices and University Management - Hamelman, Paul W. (Academy of Management Journal, 1970)
Several recent articles and studies have suggested the possibility of applying Planning - Programming - Budgeting (PPB), systems analysis and other advanced management concepts to the problems of long-range resource planning and decision making in institutions of higher learning. This paper discusses these techniques in the context of a university with multiple educational and service missions. There are no inherent difficulties in viewing the educational process as a multi-stage, matrix transformation process. Systems analytic concepts can assist in the articulation of institutional programs and objectives, contribute to the goal of balanced resource allocations, and improve coordination among decentralized university departments.